'Are we there yet?': A multimethod study of the Oxford University Press Pathways to school improvement. Issue 1 (18th October 2018) - Davis‐Singaravelu, Susila; Sammons, Pamela
Abstract: This article presents one substantive and illustrative school case study to explore in depth practitioners' engagement with Pathways—an online school improvement resource provided by the Oxford University Press (OUP). Launched in 2013, the 'four‐step system' comprises the following phases: 'audit', 'strategic planning', 'take action' and 'evaluate impact' and aims to support primary schools through a range of whole school improvement and teaching and learning tasks. The wider research project studied primary school practitioner perceptions and attitudes towards Pathways and both collective and individual improvement practice via an embedded multimethod case study comprising a purposive sample of five primary schools that signed up to use Pathways. It followed the evolution of Pathways using a 'design‐based research' (DBR) framework that focuses on bridging the realms of academia and more practical contexts, and promoting research impact through user engagement and active participation. The growth and use of Pathways by schools was investigated through the theoretical lenses of the Dynamic Approach to School Improvement (DASI) and Guskey's five‐level model of Continuing Professional Development (CPD) evaluation (2002). The Pathways research and case study in this article focus uniquely on how teaching practitioners engage with and perceive technology in their school improvement practice and professional development experiences in one particular school context. Pathways tools seemed to offer opportunities for teachers to work collaboratively, individually and autonomously—with their work being partially 'mediated' by Pathways itself, and specific 'hospitable conditions' cultivated by senior leadership such as professional support and trust.